2001
DOI: 10.1029/2000jd900761
|View full text |Cite
|
Sign up to set email alerts
|

A study of formaldehyde chemistry above a forest canopy

Abstract: Abstract. Gas-phase formaldehyde (HCHO) was measured at a mixed deciduous/coniferous forest site as a part of the PROPHET 1998 summer field intensive. For the measurement period of July 11 through August 20, 1998, formaldehyde mixing ratios ranged from 0.5 to 12 ppb at a height-10 m above the forest canopy, with the highest concentrations observed in southeasterly air masses. Concentrations varied on average from a mid-afternoon maximum influenced by photochemical production of 4.0 ppb, to a late night minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
93
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 60 publications
8
93
3
Order By: Relevance
“…Virtually all oxidation of hydrocarbons in the atmosphere involves the production of HCHO at some point in its reaction sequence. Sumner et al (2001) reported that isoprene was the most important precursor of HCHO in the same deciduous/coniferous forest as the Tan et al (2001) study, contributing 82% on average to the calculated midday HCHO production rate. However, little is known about the effect of biogenic VOCs on regional photochemistry in coniferous forests where 2-methyl-3-buten-2-ol (MBO) and monoterpenes, rather than isoprene, are predominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtually all oxidation of hydrocarbons in the atmosphere involves the production of HCHO at some point in its reaction sequence. Sumner et al (2001) reported that isoprene was the most important precursor of HCHO in the same deciduous/coniferous forest as the Tan et al (2001) study, contributing 82% on average to the calculated midday HCHO production rate. However, little is known about the effect of biogenic VOCs on regional photochemistry in coniferous forests where 2-methyl-3-buten-2-ol (MBO) and monoterpenes, rather than isoprene, are predominant.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the assumption that dry deposition is the primary sink of HCHO during night remains effectively valid. Because the nocturnal boundary layer depth is critical to estimating the nighttime dry deposition velocity, a comparative method with nighttime ozone decay rates is used to circumvent the unobserved nocturnal boundary layer depth as in previous studies (Shepson et al, 1992;Sumner et al, 2001). Assuming that nocturnal production and loss from OH cancel, we calculate the first-order loss rate constant from the averaged logarithmic [HCHO] decay during the middle of the night (01:00 ∼ 04:00) to be −0.27 h −1 .…”
Section: Observed Formaldehyde Sinks and Inferred Dry Depositionmentioning
confidence: 99%
“…On one hand, formaldehyde and acetaldehyde are usually important products in photochemical oxidations of hydrocarbons (Sumner et al, 2001;Wiedinmyer et al, 2001;Duane et al, 2002;Guo et al, 2009Guo et al, , 2013; on the other hand, they are the important participants in atmospheric photochemical reactions, e.g., photolysis and reactions with OH· (Atkinson, 2000). Intensive sunlight and high temperature were recorded in spring, summer and autumn, particularly in summer (Table 2).…”
Section: Seasonal and Diurnal Variationsmentioning
confidence: 99%
“…In addition, photochemical formation played positive roles in the distributions of formaldehyde and acetaldehyde (Guo et al, , 2013, and formaldehyde was the dominant initial carbonyl product in the photochemical oxidations of hydrocarbons with a high yield of 63-84% (Sumner et al, 2001;Wiedinmyer et al, 2001;Duane et al, 2002). Qinzhou has the lower latitude (108°39′E, 21°58′N) with the intensive sunlight and high temperature in summer (Table 2), which favors photochemical oxidations of atmospheric hydrocarbons.…”
Section: Concentration Ratiosmentioning
confidence: 99%
See 1 more Smart Citation